2002
DOI: 10.1023/a:1017976305128
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Repair of superficial damage to gastrointestinal mucosa occurs by a process called restitution. Goblet cells reside throughout the length of the intestine and are responsible for the production of mucus. However, a kinetic analysis of goblet cell dynamics of small intestine in restitution has hitherto not been reported. The aim of the present study was to investigate the role of goblet cells in the process of restitution of rat small intestine subjected to ischemia and ischemia-reperfusion injury, and therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Goblet cells are critical for the integrity and repair of the intestinal epithelium and are considered a good marker of intestinal health [18]. GC mucus depletion occurs rapidly after the onset of intestinal ischemia [19].…”
Section: Discussionmentioning
confidence: 99%
“…Goblet cells are critical for the integrity and repair of the intestinal epithelium and are considered a good marker of intestinal health [18]. GC mucus depletion occurs rapidly after the onset of intestinal ischemia [19].…”
Section: Discussionmentioning
confidence: 99%
“…This theory is supported by the negative correlation between IFABP and ITF serum level. Ikeda et al established that during the kinetic analysis of goblet cell dynamics of the small intestine in restitution, goblet cells may play an important role in restitution after an ischemic reperfusion injury, but under ischemic conditions these cells could not provide protective function ( 27 ). Similarly, Varga et al also detected during intestinal ischemia a decrease in the numbers of goblet cells responsible for synthesis of trefoil factor peptides ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other components within the mucous gel include water, electrolytes, sloughed epithelial cells and secreted immunoglobulins. Mucus produces a physical and chemical barrier that protects the epithelium from physical damage by luminal content, guards against bacterial invasion, regulates epithelial hydration, and interacts with secreted immunoglobulin A to produce antibody and antitoxin effects [ 23 , 31 , 32 ]. Recently, Yang and Yu [ 33 ] indicated that the perspective regarding GCs and their products has changed, suggesting that they are not passive cells but play a positive role in maintaining intestinal tract immunity and mucosal homeostasis.…”
Section: Introductionmentioning
confidence: 99%